Profit over Privacy : How Surveillance Advertising Conquered the Internet - Crain, Matthew (Book collections on Project MUSE., 2021)
"Profit over Privacy gives internet surveillance a much-needed origin story by chronicling the development of its most important historical catalyst: web advertising"--